The expression pattern of GDF15 in human brain changes during aging and in Alzheimer’s disease - Chiariello, Antonio; Valente, Sabrina; Pasquinelli, Gianandrea; Baracca, Alessandra; Sgarbi, Gianluca; Solaini, Giancarlo; Medici, Valentina; Fantini, Valentina; Poloni, Tino Emanuele; Tognocchi, Monica; Arcaro, Marina; Galimberti, Daniela; et al. (Frontiers in Aging Neuroscience, 2023)
Growth Differentiation Factor 15 (GDF15) is a mitochondrial-stress-responsive molecule whose expression strongly increases with aging and age-related diseases, however, its role in neurodegenerative diseases, including Alzheimer’s disease (AD) is still debated. We have characterized the expression of GDF15 in brain samples from AD patients and non-demented subjects (controls) of different age. Although no difference in CSF levels of GDF15 was found between AD patients and controls, GDF15 was expressed in different brain areas and seems to be predominantly localized in neurons. The ratio between its mature and precursor form was higher in frontal cortex from AD patients compared to age-matched controls (p<0.05). Moreover, this ratio was even higher for centenarians (p<0.01), indicating that also aging affects GDF15 expression and maturation. A lower expression of OXPHOS complexes I, III and V in AD comparing to controls was also noticed, and a positive correlation between GDF15 and IL-6 mRNA levels was observed. Finally, when GDF15 was silenced in vitro in dermal fibroblasts, a decrease of OXPHOS complexes transcript levels and an increase in IL-6 levels was observed. In conclusion, although GDF15 seems not to be a reliable CSF marker for AD, it is highly expressed in aging and AD brains, likely as a part of stress response aimed to counteract mitochondrial dysfunction and neuroinflammation.